Factors Determining the Greater Participation of Women in Local Government Presidential Elections in Poland - Niewiadomska-Cudak, Małgorzata (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
The issue of women’s representation in the bodies of executive power in Polish local government is generating increasing interest in the context of women’s activity in local politics. The purpose of the publication is to explain the reasons affecting the low representation of women in local presidential elections. The author answers the question of the low representation of women in mayoral elections and examines whether existing stereotypes about the role of women in society are the main barrier affecting the decision to run in these local government elections. Are there also other reasons that hinder running for the city’s executive body? With the research questions posed in this way, the author aims not only to initiate a discussion on women’s participation in local government bodies, but also to determine the reasons for their underrepresentation and to identify effective methods of counteracting this phenomenon once the barriers are identified. Problematyka reprezentacji kobiet w organach władzy wykonawczej w polskim samorządzie wywołuje coraz większe zainteresowanie w kontekście aktywności kobiet w polityce lokalnej. Celem publikacji jest wyjaśnienie przyczyn wpływających na niewielką reprezentację kobiet w samorządowych wyborach prezydenckich. Autorka odpowiada na pytanie dotyczące niskiej reprezentacji kobiet w wyborach na urząd prezydenta miasta oraz bada czy istniejące stereotypy dotyczące roli postrzegania kobiet w społeczeństwie są główną barierą wpływającą na podjęcie decyzji o starcie w tych elekcjach samorządowych. Czy są także inne przesłanki, które utrudniają start w wyborach do organu wykonawczego w mieście? Dzięki tak postawionym pytaniom badawczym autorka pragnie nie tylko zainicjować dyskusję na temat uczestnictwa kobiet w organach władzy samorządowej, ale także ustalić przyczyny ich niedoreprezetnowania oraz wskazać skuteczne metody przeciwdziałania temu zjawisku po zidentyfikowaniu barier.
Czynniki determinujące większy udział kobiet w samorządowych wyborach prezydenckich w Polsce
Keywords: local government elections; executive authority; female candidate; female mayor; female participation; wybory samorządowe; organ władzy wykonawczej; kandydatka; prezydentka miasta; partycypacja kobiet